Класифікація екосистем Галицько-Слобожанського екокоридору - Дідух, Я.П.; Куземко, А.А. (Український фітоценологічний збірник, 2005)
Разработана классификация экосистем Галицко-Слобожанской экосети на основе европейских подходов с использованием классификации местообитаний EUNIS, в которую были внесены некоторые поправки, а также проведена ее адаптация для Украины. Классификация разработана до седьмого уровня. Она включает 7 единиц I уровня, 24 единицы — II, 58 — III, 67 — IV, 107 — VI и 359 единиц VII уровня. It was development the classification of the Halychina-Slobozhanshina econetwork's ecosystems on the basis of European approach with inplementation EUNIS Habitat classification, but some impruvements and adoption for Ukiraine have been made. The detailed classification to seventh level has been presented. It consists of 7 units of I level, 24 units of II level, 58 units of III level, 88 units of IV level, 67 units of V level, 107 units of VI level and 359 units of VII level.